THE SYMBOLISM OF WATER IN THE GOSPEL OF JOHN - Zheng , Maogui; Budiraharjo, Markus (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2024)
This study explores the symbolism of water in the Gospel of John, revealing its role in disclosing Jesus’ identity and message. Through word study, literature analysis, and qualitative methods, the research examines narratives involving the term “water”, incorporating insights from Jewish and Christian traditions. The findings suggest that water symbolizes the Holy Spirit, rebirth, new life, and other spiritual meanings within the Fourth Gospel. This analysis offers valuable insights for readers interested in the symbolic use of water in John’s Gospel and provides believers with a deeper understanding of its theological significance. By examining how water serves as a profound narrative device, the study illustrates how the Gospel of John employs this element to bridge the literal and the spiritual, emphasizing the essence of Jesus’ mission and the transformative power of faith. This research contributes to the broader understanding of Johannine symbolism, highlighting the intricate ways in which simple elements like water can convey complex theological themes and spiritual truths.